Structural Design and Performance Parameters of Controllable Hydraulic Oscillator - He Xin; Liu Gonghui; Chen Tian; Li Jun; Wang Wei (Shiyou jixie)
Hydraulic oscillators are widely used in drilling of horizontal wells and extended-reach wells， to effectively solve the problem of backing pressure of pipe strings and improve drilling efficiency. A conventional hydraulic oscillator starts to work immediately after it is run in hole for circulation， with uncontrollable working state and low effective service life. To address this issue， a controllable hydraulic oscillator is designed. This tool has two working states： vibrational， and dormant， which are switched by controlling the rotation of the disc valve， and can meet the drilling needs under different conditions. The force during the movement of the disc valve was analyzed， and the disc valve movement mathematical model was built. Based on the analysis of the structure and working principle of the tool， together with the principle of fluid mechanics， the output performance of the tool was analyzed through examples， and a number of hydraulic structure parameters that have obvious effects on the oscillation frequency and pressure drop of the tool were examined. The results show that the oscillation frequency of the turbine-driven hydraulic oscillator is only related to the displacement of drilling fluid， that is， the oscillation frequency increases with the increase of drilling fluid displacement. The pressure drop of the tool increases with the increase of drilling fluid displacement and density， and decreases with the increase of the area of the throttle orifice on the mandrel sidewall. The research findings are referential for the design and application of controllable hydraulic oscillators.